BYSTROV VIBROSEISMIC LANDFILL OF THE GEOPHYSICAL SURVEY FEDERAL RESEARCH CENTRE RAS AS A UNIQUE FACILITY FOR THE DEVELOPMENT AND EXPERIMENTAL TESTING OF NEW GEOPHYSICAL TECHNOLOGIES - V. M. Soloviev; A. F. Emanov; V. S. Seleznev; A. A. Emanov; D. G. Korabelschikov (Геодинамика и тектонофизика, 2022)
Information is presented about the Bystrov vibroseismic landfill near Novosibirsk, which houses Large-Scale Research Facilities with no analogues in the world – powerful 50–100-ton vibration sources (GRV-50, CVM-100, CV-40). The infrastructure of the landfill, the composition of the equipment, the tasks of scientific research, Russian and foreign performers of developments are described. The main research results of fundamental and practical importance are presented. One of the main tasks that the created polygon is aimed at is active vibroseismic monitoring with powerful vibrators. The repeatability and accuracy of monitoring, which is one millisecond in kinematic parameters, is shown; the existing monitoring scheme and prospects for increasing the monitoring area due to a stationary seismological network of stations are presented. An example of one of the promising fundamental developments is shown – the study of seismic emission during the excitation of a powerful low-frequency impact on the environment.